Skin and respiratory exposure to soluble lead, cobalt, nickel, copper, arsenic and silver at two South African precious metals refineries - Linde, Stephanus J. L.; Franken, Anja; du Plessis, Johannes L. (International archives of occupational and environmental health, 2023)
Objectives Precious metals refinery workers are exposed to soluble platinum group metals (PGMs) during PGM-refining but may also be exposed to hazardous non-PGMs (Pb, Co, Ni, Cu, As and Ag) still present in the matte following base metals refining. The aim of this article was to report the skin and respiratory exposure of workers to soluble non-PGMs during PGM-refining. Methods Skin and respiratory exposure (of 40 workers at two precious metals refineries) were measured simultaneously over two consecutive shifts. Skin exposure was measured on the palm, wrist, neck and forehead using Ghostwipes™ and respiratory exposure was measured using the MDHS method 46/2 during which soluble metals were extracted using 0.07 M HCl and mechanical agitation, followed by ICP–MS analysis. Results The geometric means (GM) of average skin exposure to individual soluble metals on all anatomical areas was found in the order Cu (0.018 µg/cm 2 ) > Ni (0.016 µg/cm 2 ) > Pb (0.008 µg/cm 2 ) > Ag (0.006 µg/cm 2 ) > As (0.004 µg/cm 2 ) > Co (0.0008 µg/cm 2 ) with the palm being the highest exposed anatomical area. The order of the GM respiratory exposure was Pb (0.224 µg/m 3 ) > Ag (0.201 µg/m 3 ) > Cu (0.159 µg/m 3 ) > As (0.079 µg/m 3 ) > Ni (0.034 µg/m 3 ) > Co (0.016 µg/m 3 ) with exposure to As exceeding the South African occupational exposure limit (20 µg/m 3 ) during concentrate handling (max 66.174 µg/m 3 ). Conclusions Workers were exposed to a mixture of toxic PGM and non-PGMs via the skin and inhalation. Exposure to these metals could lead to the development of diseases, such as contact dermatitis, occupational allergy, or occupational cancer. Non-PGMs must be included in hazardous chemical risk assessments and control strategies implemented at precious metals refineries.